2021
DOI: 10.1002/cctc.202101501
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical, Water‐Assisted Asymmetric Transfer Hydrogenation of Ketones Using Ruthenium Catalyst

Abstract: Dedicated to the memory of Prof. Ferenc FülöpAsymmetric catalytic reactions are among the most convenient and environmentally benign methods to obtain optically pure compounds. The aim of this study was to develop a green system for the asymmetric transfer hydrogenation of ketones, applying chiral Ru catalyst in aqueous media and mechanochemical energy transmission. Using a ball mill we have optimized the milling parameters in the transfer hydrogenation of acetophenone followed by reduction of various substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
6
0
3
Order By: Relevance
“…For this study, the process mass intensity (PMI) reaction of 97.3 and 166.2 by co-cultivation strategy and conventional method was calculated. Comparatively, the work of Onisuru et al and Kolcsár, Szőllősi by using organometallic catalysts had also been assessed, with the PMI reaction of 272.6 and 2499.4, respectively. , Analysis of PMI results expressed the eco-friendliness of the co-cultivation strategy regarding other data in the literature and exhibited the potential of this novel biocatalytic method on the preparation of aryl alcohol. The analysis of green chemistry metrics on different above methods are supported in the Supporting Information Spreadsheet.…”
Section: Resultsmentioning
confidence: 93%
“…For this study, the process mass intensity (PMI) reaction of 97.3 and 166.2 by co-cultivation strategy and conventional method was calculated. Comparatively, the work of Onisuru et al and Kolcsár, Szőllősi by using organometallic catalysts had also been assessed, with the PMI reaction of 272.6 and 2499.4, respectively. , Analysis of PMI results expressed the eco-friendliness of the co-cultivation strategy regarding other data in the literature and exhibited the potential of this novel biocatalytic method on the preparation of aryl alcohol. The analysis of green chemistry metrics on different above methods are supported in the Supporting Information Spreadsheet.…”
Section: Resultsmentioning
confidence: 93%
“…18 Transfer hydrogenations of various reactants, such as carbonyls, ketones, and nitro derivatives have been increasingly discussed in the literature. 18,[20][21][22] However, a key question remains whether transfer hydrogenation is truly a preferred Green method of hydrogenation when compared to using elemental hydrogen. Indeed, transfer hydrogenation reagents suffer from pitfalls such as high cost, high molecular weight (compared to H 2 ), and the fact that elemental hydrogen tends to be involved in their main synthesis routes.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanochemistry induced by a mechanical force is an efficient, simple, green, and energy-saving method for physicochemical and chemical transformations on a large scale, [17][18][19] and has been widely applied in chemical production and numerous research fields such as organic synthesis, [20][21][22] inorganic synthesis, [23][24][25] advanced energy materials, [26,27] metalorganic frameworks, [28,29] and gas synthesis. [30][31][32] Pfennig et al reported a mechanochemical method to prepare Grignard reagents from organobromides and subsequently react with gaseous CO 2 or sodium methyl carbonate to obtain aryl and alkyl carboxylic acids reaching 82 % yield.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanochemistry induced by a mechanical force is an efficient, simple, green, and energy‐saving method for physicochemical and chemical transformations on a large scale, [17–19] and has been widely applied in chemical production and numerous research fields such as organic synthesis, [20–22] inorganic synthesis, [23–25] advanced energy materials, [26,27] metal‐organic frameworks, [28,29] and gas synthesis [30–32] . Pfennig et al .…”
Section: Introductionmentioning
confidence: 99%